2020
DOI: 10.1002/cpns.110
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Ca2+ Imaging and Optogenetic Stimulation of Cortical Astrocytes in Adult Murine Brain Slices

Abstract: Astrocytes are actively involved in a neuroprotective role in the brain, which includes scavenging reactive oxygen species to minimize tissue damage. They also modulate neuroinflammation and reactive gliosis prevalent in several brain disorders like epilepsy, Alzheimer's, and Parkinson's disease. In animal models, targeted manipulation of astrocytic function via modulation of their calcium (Ca2+) oscillations by incorporating light‐sensitive cation channels like Channelrhodopsin‐2 (ChR2) offers a promising ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…However, ChR2 can also allow the influx of Ca 2+ , which has been shown to cause the release of gliostransmitters like ATP (Gourine et al, 2010 ; Chen et al, 2013 ) and glutamate (Haydon and Carmignoto, 2006 ). ChR2 stimulation in astrocytes has been reliably shown to induce changes in intracellular Ca 2+ (Li D. et al, 2012 ; Figueiredo et al, 2014 ; Perea et al, 2014 ; Mederos et al, 2019 ; Balachandar et al, 2020 ); these changes have been observed to enhance both excitatory and inhibitory synaptic transmission in the primary visual cortex (Perea et al, 2014 ). The use of ChR2 to activate astrocytes has also been shown to induce the release of ATP (Gourine et al, 2010 ; Figueiredo et al, 2014 ).…”
Section: Optogenetics and Dreadds: Physiologically Relevant For The Study Of Astrocytes?mentioning
confidence: 99%
“…However, ChR2 can also allow the influx of Ca 2+ , which has been shown to cause the release of gliostransmitters like ATP (Gourine et al, 2010 ; Chen et al, 2013 ) and glutamate (Haydon and Carmignoto, 2006 ). ChR2 stimulation in astrocytes has been reliably shown to induce changes in intracellular Ca 2+ (Li D. et al, 2012 ; Figueiredo et al, 2014 ; Perea et al, 2014 ; Mederos et al, 2019 ; Balachandar et al, 2020 ); these changes have been observed to enhance both excitatory and inhibitory synaptic transmission in the primary visual cortex (Perea et al, 2014 ). The use of ChR2 to activate astrocytes has also been shown to induce the release of ATP (Gourine et al, 2010 ; Figueiredo et al, 2014 ).…”
Section: Optogenetics and Dreadds: Physiologically Relevant For The Study Of Astrocytes?mentioning
confidence: 99%
“…Simulation results predict that calcium dynamics in astrocytes, as seen in experimental studies [33,64,65], can be heavily regulated by light-induced activation of ChR2. Consistent in all simulations performed in this study, upon light activation, astrocytes underwent increases in their basal calcium level and exhibited changes in the spiking activity (Figs 2 and 3).…”
Section: Salient Features Of Light-evoked Calcium Signaling In Astrocmentioning
confidence: 84%
“…[30], namely WT 1 and WT 2 . Using the model, we analyze the effect of light stimulation in astrocytes congruent with experimental recording durations (in the order of tens of minutes) [31][32][33], and also gauge the potential effect of long-term optogenetic stimulation (in the order of several hours or beyond) in these cells. Secondly, we quantify the effect of varying stimulation light intensities on a ChR2-incorporated astrocyte with respect to its spiking rate and basal level.…”
Section: Introductionmentioning
confidence: 99%
“…Involved in the internalization and trafficking of activated tyrosine kinase receptors such as PDGFRB. A team designed cellular experiments and found lower Rho-related protein HP1 levels in astrocytes than in normal groups, which may be clinically meaningful for some neurological diseases, including epilepsy and Alzheimer's disease [ 65 ].…”
Section: Discussionmentioning
confidence: 99%